Single intraoperative infrared laser optimized bone repair in rat femoral osteotomies with experimentally induced osteoporosis - Polo, Tárik Ocon Braga [UNESP]; Fonseca-Santos, João Matheus [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; da Silva, William Phillip Pereira [UNESP]; Barbosa, Stefany [UNESP]; Santos, Anderson Maikon de Souza [UNESP]; Silva, Mirela Caroline [UNESP]; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP]; Faverani, Leonardo P. [UNESP] (Springer Nature, 2023)
This study aimed to evaluate the effect of infrared laser (IRL) on bone repair in ovariectomized rats subjected to femoral osteotomies. Of 32 rats, half underwent bilateral ovariectomy (OVX) and the other half underwent sham ovariectomy (SHAM). A period of 3 months was defined to observe the presence of osteoporosis. The rats were subjected to osteotomies in the femurs and then fixed with a miniplate and 1.5-mm system screws. Thereafter, half of the rats from both SHAM and OVX groups were not irradiated, and the other half were irradiated by IRL using the following parameters: wavelength, 808 nm; power, 100 mW; 60 s for each point; 6 J/point; and a total of 5 points of bone gap. All animals were euthanized 60 days after surgery. The femur gap was scanned using micro-computed tomography (micro-CT). The samples were then examined under a confocal laser microscope to determine the amounts of calcein and alizarin red. The slides were stained with alizarin red and Stevenel’s blue for histometric analysis. In the micro-CT analysis, the OVX groups had the lowest bone volume (P < 0.05). When the laser was applied to the OVX groups, bone turnover increased (P < 0.05). New bone formation (NBF) was comparable between SHAM and OVX/IR (P > 0.05) groups; however, it was less in the OVX groups (P < 0.05). In conclusion, the results encourage the use of IRL intraoperatively as it optimizes bone repair, mainly in animals with low bone mineral density.
Keywords: Bone regeneration; Fracture fixation internal; Laser therapy; Osteoporosis